The Effect of Podcast Rintik Sedu on the Behavior of Celebrity Worship K-Popers (Episode When You Fall in Love with Your Idol) - Ingratubun, Rafiqah Rizqy S.; Aprianti, Agus (Budapest International Research and Critics University, 2022)
The rapid growth of communication and news technology at this time certainly has a major impact on all areas of life. Online media in Indonesia, this development has succeeded in combining several media platforms. Podcasts is an on-demand service, which means listeners can select, loop, and skip content which want to they hear. The purpose of this research is to get information and To do analysis about influence communication in Rintik podcast sad to behavior k- poppers. This research includes causal associative research with quantitative descriptive approach. The sample in this study has criteria, including male or female, aged 17-25 years, listening to the Rintik Sedu podcast and a K-poper so that 100 respondents were obtained. The analysis used multiple linear regression. The results of this study indicate that the Rintik Sedu podcast has a positive and significant influence on celebrity worship. This is because podcasts have a more efficient one-time production rate, podcasts must be able to upload at least daily, weekly or monthly to keep listeners loyal, podcasts can have a good impact because listeners can directly download podcasts they want to hear and podcasts that can be listened to. anywhere and anytime has succeeded in captivating the listener's desire because it can be listened to at will wherever and whenever.